Pengaruh Pembinaan Disiplin dan Motivasi Kerja terhadap Kinerja Guru SMK Tunas Bangsa Ngamprah - Rahayu Nugroho Putri; R.M Juddy Prabowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the impact of discipline and encouragement training on teacher performance at SMK Tunas Bangsa Ngamprah. A quantitative approach was used involving 38 honorary teachers and a principal as research subjects. Data were collected through a survey that was tested for validity and consistency. The research findings revealed a significant positive effect of discipline and encouragement training on teacher performance. Statistical tests showed a significance value of less than 0.05, indicating that increasing work encouragement and disciplinary training can significantly improve teacher performance. Based on these results, it is recommended that the school continue to strengthen the motivation and discipline of teachers to improve their performance, which in turn will improving the quality of education have an impact at SMK Tunas Bangsa Ngamprah. Keywords: Discipline Development, Work motivation, Teacher Performance, Education, Tunas Bangsa Ngamprah Vocational School